2009
DOI: 10.4163/kjn.2009.42.8.723
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Food and Nutrient Intakes between Instant Noodle Consumers and Non-Consumers among Korean Children and Adolescents

Abstract: Instant noodle is one of the most popular foods in Korea. The objective of this study was to examine the association of instant noodle consumption and food and nutrient intake among children and teenagers in Korea. We used dietary data from 24-h recall of 1,748 subjects aged 7-19 years who participated in the 2005 Korea National Health and Nutrition Examination Survey. Those who consumed instant noodle once or more during the survey period were categorized as "instant noodle consumer (INC)" and were compared f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…The combined effect of high energy density (381-464 kcal/100 g) (41), high glycemic loads with refined carbohydrates, high saturated fat content (66.2-87.2 kcal/100 g) (42), and high sodium (1.7-2.5 g/serving) (43) may contribute to an increased risk of metabolic syndrome and abdominal obesity. Even though measurements of the glycemic index of instant noodles varied among studies (44)(45)(46)(47)(48)(49)(50)(51), the overall glycemic load of instant noodles is high, given their high carbohydrate content (35,(38)(39)(40)(41)(42)(43). In our study, the association between instant noodles and metabolic syndrome differed significantly between genders, and there was no effect modification of this association by age, BMI, or physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…The combined effect of high energy density (381-464 kcal/100 g) (41), high glycemic loads with refined carbohydrates, high saturated fat content (66.2-87.2 kcal/100 g) (42), and high sodium (1.7-2.5 g/serving) (43) may contribute to an increased risk of metabolic syndrome and abdominal obesity. Even though measurements of the glycemic index of instant noodles varied among studies (44)(45)(46)(47)(48)(49)(50)(51), the overall glycemic load of instant noodles is high, given their high carbohydrate content (35,(38)(39)(40)(41)(42)(43). In our study, the association between instant noodles and metabolic syndrome differed significantly between genders, and there was no effect modification of this association by age, BMI, or physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a study of Korean adults, those with frequent instant noodle consumption were shown to have significant differences in the intakes of nuts, fruits, vegetables, protein, calcium, phosphorus, iron, potassium, vitamin A, and vitamin C [7]. Moreover, in a study of Korean children and adolescents, instant noodle consumption was associated with significant differences in the intake of fruits, vegetables, calcium, and vitamin C [19]. These food groups and nutrient deficiencies based on instant food consumption are all supported by the findings of our own study.…”
Section: Discussionmentioning
confidence: 95%
“…However, there has been no research on the selection attributes of instant noodles. In addition, research on the behavior of noodle product consumers has been mostly limited to exploratory research, such as the frequency of ingestion for instant noodles Lee et al, 2009;Chung, Lee, & Cho, 2010). Studies on the selection attributes of ramen affecting consumer satisfaction and repurchase have been few and limited.…”
Section: Selection Attributes For Instant Noodlesmentioning
confidence: 99%